Effect of irrigation and drainage requirement on water-use efficiency and yield of pure and maize (Zea mays) - based intercrops - SINGH, J P; PRASAD, U K; SINGH, H (The Indian Journal of Agricultural Sciences, 2013)
A field experiment with 3 levels of water management practices (rainfed with and without drainage, and irrigation with drainage) and 5 cropping systems -maize (Zea mays L.), groundnut (Arachis hypogaea L.), turmeric (Curcuma Jonga L), maize +turmeric ana maize + groundnut was conducted during rainy season of 1990-92. Leaf area index and dry-matter production of all the crops were maximum under irrigation and proper drainage system, Maize-equivalent yield was Significantly highest (8,2 tonnes/ha) in case of maize + tunneric as compared to sole crops as well as maize +groundnut intercropping system during first year. However, during second year, difference between maize + turmeric and maize + groundnut system was not pronounced. Net return during first year did not differ between maize + groundnut and maize + turmeric but during second year maize + groundnut excelled in net return as compared to maize + turmeric.Irrigation with drainage provision resulted in maximum yield equivalence (7.5 tonnes/ha) and net return (Rs 11 752)as compared to other treatments. The water-use efficiency was maximum in case of pure crop of turmeric (0.499 tonne/ha/cm) while in second year it was maximum (0.583 tonne/ha/cm) under sale crop of groundnut.